Does gynaecological cancer care meet the needs of Indigenous Australian women? Qualitative interviews with patients and care providers - Beverley Marcusson-Rababi; Kate Anderson; Lisa J. Whop; Tamara Butler; Nicole Whitson; Gail Garvey (BMC, 2019)
Abstract Background There is a disparity in the burden of gynaecological cancer for Indigenous women compared with non-Indigenous women in Australia. Understanding how Indigenous women currently experience gynaecological cancer care services and factors that impact on their engagement with care is critical. This study explored Indigenous Australian women's experience of gynaecological cancer care at a major metropolitan hospital in Queensland. Methods Indigenous women receiving care at a major metropolitan Queensland hospital for investigation or diagnosis of gynaecological cancer were invited to participate in a larger longitudinal study exploring women's experiences of gynaecological cancer care. This component was an in-depth, qualitative interview exploring the women's experiences of hospital care at approximately three-month post initial referral. A peer-approach was used to interview women. Hospital-based care providers involved in the care of Indigenous gynaecological cancer patients were invited to be interviewed. Interviews were transcribed and thematically analysed using an interpretative phenomenological approach enabling a multi-layered, contextualised understanding of the patients' experience and their interaction with tertiary cancer services. Results Eight Indigenous patients and 18 care providers were interviewed. Analysis of all interviews revealed four broad issues affecting Indigenous patients' early experiences of care: (1) navigating the system, impacted by timely diagnosis, access to support services and follow up; (2) communication and decision-making, patients' decision-making, efficacy of doctor-patient communication, and patients' knowledge about cancer; (3) coping with treatment demands, was impacted by emotional stress, access to services and support by hospital staff; and (4) feeling welcome and safe in the hospital, impacted by patients' relationship with care providers and their access to culturally-safe services. The combination of factors impacting these women's' experience of gynaecological care commonly left these women at breaking point, often with limited access to information, resources or support. Conclusions Our findings revealed that experiences of cancer care for Indigenous women are overlain by challenges associated with late referral, misdiagnosis, miscommunication, lack of information, logistics in accessing treatment and services and system cultural insensitivities. Our findings offer insights that can inform cancer care provision to more effectively support Indigenous women accessing gynaecological cancer services.